1145Obesity-related changes in metabolomic profiles in youth. (2nd September 2021) - Mansell, Toby; Sabin, Matthew; McCallum, Zoe; Juonala, Markus; Burgner, David; Saner, Christoph
Abstract: Background: Obesity during childhood and adolescence is linked to subclinical atherosclerosis, metabolic dysfunction and later cardiovascular disease. Adults with obesity have metabolomic profiles that predict cardiovascular disease and mortality. Analogous data from children with obesity are sparse. Here, we aimed to investigate i) the relationship between the severity of obesity (determined by the percentage above the 95 th BMI-centile (%>95 th BMI-centile)) and metabolomic profiles, ii) the effect of changes in the severity of obesity on the metabolomic profile and iii) the relationship between obesity-related metabolites and subclinical atherosclerosis outcomes. Methods: Participants from the Childhood Overweight Biorepository of Australia (COBRA) cohort had %>95 th BMI-centile and NMR metabolomic profile (Nightingale, Finland) from fasted blood analysed at two time-points (mean interval of 5.5 years). At the follow-up visit, subclinical atherosclerosis phenotypes (carotid elasticity, carotid intima-media thickness, and pulse-wave velocity) were assessed. Results: There were 98 participants who attended both visit 1 (mean %>95 th BMI-centile 134.6±19.0) and visit 2 (mean %>95 th BMI-centile 130.7±26.2). Higher absolute, and increasing severity, of obesity between visits were associated with increased phenylalanine, tyrosine, GlycA (a marker of chronic inflammation), and pyruvate, in both sexes (estimated increases of 0.14-0.18 standard deviations per 10% BMI-centile at visit 2, and 0.15-0.25 per 10% increase in BMI-centile between visits). There was modest evidence for a relationship between lower alanine and higher carotid elasticity. Conclusions: In children with obesity, the overall severity of obesity and changes in obesity severity were associated with a metabolomic pattern that in adults is predictive of cardiovascular disease. In children, these metabolites were not related subclinical atherosclerosis; these relationships may become manifest with increasing age. Key messages: There is evidence for an early effect of severe obesity on metabolomic profiles in childhood and adolescence.